A comprehensive study on characterization of biosynthesized copper-oxide nanoparticles, their capabilities as anticancer and antibacterial agents, and predicting optimal docking poses into the cavity of S. aureus DHFR - Ehab S. Gad; Salem S. Salem; Samy Selim; Mohammed S. Almuhayawi; Mohammed H. Alruhaili; Soad K. Al Jaouni; Amna A. Saddiq; Medhat E. Owda (PLoS ONE, 2025)
The eco-friendly method of producing copperـoxide nanoparticles through the use of okra fruit extract is a simple, economical, rapid, and sustainable technique. The resultant copperـoxide nanoparticles (CuO NP) were analyzed with several analytical methods, such as UV-vis spectroscopy, FourierـTransform Infrared Spectroscopy (FT-IR), and X-Ray Diffraction (XRD), Zeta potential, TransmissionـElectron Microscopy (TEM) and EnergyـDispersive X-ray (EDX) analysis. The CuO NP exhibited a maximum absorbance at 381 nm. The formation of CuO NP was further confirmed by characteristic bands observed at 534 and 588 cm-1. The monoclinic structure of the CuO NP was identified with prominent peaks detected at 2θ values of 32.47°, 35.43°, 38.64°, 48.68°, 53.38°, 58.14°, 61.39°, 66.11°, 67.82°, 72.27°, and 74.96°. The overall findings indicate that the nanoparticles had an average diameter in the approximate range of 10 to 30 nm based on the TEM analysis. The cytotoxicity study, conducted on Human Fibroblast normal HFB4 cell lines, indicated that the halfـmaximal inhibitory concentration (IC50) dose was 236.34 μg/mL. An IC50 dose of 109.46 μg/mL was found in antitumor effect studies using breast adenocarcinoma Mcf- 7 cell lines, revealing a good level of safety for CuO NP. According to the antibacterial study, Staphylococcus aureus and Bacillus cereus had inhibition zone diameters (IZDs) of 29.5 ± 0.7 mm and 24.6 ± 1.2 mm, respectively, making them the most vulnerable bacteria to CuO NP. In contrast, P. aeruginosa was the least sensitive strain, with a minimum IZD of 15 ± 1.6 mm. Compared to gram-negative infections, the CuO NPs were found to have a significantly higher antibacterial effectiveness versus Gram -positive pathogens. Molecular docking against dihydrofolate reductase (DHFR) of Staphylococcus aureus (PDB ID: 6P9Z) illustrated that the CuO NP was partially interlocked with the active site of 6P9Z by the fitting energy value of -44.93 kcal/mol through five classical hydrogen bonds with Ala7, Gln9, Thr46, Ser49, and Phe92. The last one is also generated by the marketing antifolate agent methotrexate (MTX), adding some MTX-like character to the CuO NP inhibitor.